Living with Polyneuropathy Organomegaly Endocrinopathy Monoclonal gammopathy Skin changes (POEMS) syndrome: a case study of healthcare experiences and quality of life. Issue 17 (14th August 2021) - Twigg, Jessica; Methley, Abigail; Lavin, Tim; Dickinson, Gemma; Teager, Alistair
Abstract: Aim: Polyneuropathy Organomegaly Endocrinopathy Monoclonal gammopathy Skin changes (POEMS) Syndrome is a rare condition with an estimated prevalence rate of 0.3 per 100, 000 people. Patient perspectives on healthcare experiences and quality of life have not yet been studied in depth. This novel study aimed to explore one person's lived experience of Polyneuropathy Organomegaly Endocrinopathy Monoclonal gammopathy Skin changes (POEMS) Syndrome, taking into consideration healthcare experiences in relation to diagnosis and treatment. Method: A mixed-method design was used; one participant completed a semi-structured interview and three self-report measures: Hospital Anxiety and Depression Scale; World Health Organisation Quality of Life Scale (brief); Brief Illness Perception Questionnaire. Results: Three qualitative themes appeared to influence the participant's healthcare experiences and quality of life: (1) Diagnosis and treatment, (2) identity and adjustment, and (3) recovery. Diagnosis and treatment summarised the patient's journey to receiving her diagnosis and the difficulties with treatment for this condition. Identity and adjustment included pre and post-diagnosis identity, frustrations and coping strategies. Recovery included experiences of progression and decline and service provision. Conclusion: All Multidisciplinary Team (MDT) interventions for Polyneuropathy Organomegaly Endocrinopathy Monoclonal gammopathy Skin changes (POEMS) Syndrome should be person-centred and focus on identity and personal strengths. Further research and service development should be completed to increase awareness and understanding of Polyneuropathy Organomegaly Endocrinopathy Monoclonal gammopathy Skin changes (POEMS) Syndrome, promote patient wellbeing, reduce psychological distress, and facilitate engagement in neurorehabilitation. Implications for rehabilitation: Polyneuropathy Organomegaly Endocrinopathy Monoclonal gammopathy Skin changes (POEMS) Syndrome is a rare condition and incorrect diagnoses and treatment have a significant impact on patients' physical and psychological wellbeing. Patients and families require support through person-centred care and good communication and continuity of care between multiple services. Multi-disciplinary interventions which focus on identity and strengths were beneficial for the participant in this case study. Further research and education are needed to increase knowledge on patient experiences of Polyneuropathy Organomegaly Endocrinopathy Monoclonal gammopathy Skin changes (POEMS) Syndrome and continue to improve service provision.